Project Based Learning Evaluation in Developing Student Creative - Meike Imbar (PT. NALURI EDUKASI PRESS, 2025)
This study aims to analyze the evaluation of project-based learning in developing student creativity through a comprehensive literature review. The research method uses a qualitative approach with a type of literature study, involving a systematic analysis of various academic sources relevant to project-based learning and the development of student creativity. Data collection techniques are carried out through documentation studies by reviewing journal articles, reference books, and scientific publications that can be accessed through academic databases. Data analysis uses thematic analysis techniques that include data reduction, data presentation, and drawing conclusions with source triangulation to ensure the validity and reliability of the findings. The results of the study indicate that project-based learning has significant effectiveness in improving student creativity, with an increase of up to 25% compared to conventional learning. This learning successfully develops various dimensions of creativity holistically, including originality, flexibility of thinking, elaboration, and sensitivity to problems. Effective evaluation strategies include the use of a multi-dimensional creativity rubric, portfolio assessment, peer assessment, and self-reflection that provide a comprehensive approach to measuring the development of student creativity. This study contributes to the development of a project-based learning evaluation framework that can optimize the development of student creativity in the context of 21st-century education.